Physico-chemical properties of phosphate solutions used in KDP single crystal growth - Pantaler, R.P.; Smirnova, O.M.; Blank, A.B. (Functional Materials, 2004)
Basing on known experimental data, mathematical dependences have been derived for determination of the solution compositions in the K₂O-P₂Og-H₂O system. Equations have been proposed to calculate the solubility and the density of the saturated KH₂PO₄ solutions within wide ranges of the solution pH and temperature. The ion equilibrium calculations for KH₂PO₄ phosphate solutions evidence the formation possibility of protonated phosphate dimer forms that favor the KH₂PO₄ solubility increase. The results obtained supply the known literature data on the acidity effect on the composition and physicochemical properties of the K₂O-P₂O₅-H₂O system solutions and could be applied to optimize the growing conditions of KDP single crystals from aqueous solutions.